Asset Growth Anomaly of Corporate Bonds: A Decomposition Analysis - Chen, Fang; Huang, Jingzhi; Li, Yifei; Wu, Wenfeng; Yu, Tong (The Review of Asset Pricing Studies, 2026)
This study examines the relationship between corporate asset growth rates and bond performance, uncovering a strong inverse relationship between the two. Higher asset growth increases asset value, potentially offering greater protection to bondholders and leading to lower bond returns. By decomposing bond returns into initial yields and subsequent yield changes, our analysis supports this expectation and suggests that investors may overreact to asset growth, as investor sentiment significantly influences bond yields in response to it. Finally, drawing on insights from leverage-based Q-theory, we examine how stock returns respond to asset growth, accounting for its effect on bond performance. (JEL G12, G02)